Design of a Web-Based Archive Information System at the Ta Village Office, Tanete Riattang District, Bone Regency: Information systems, archives, web-based - Iqbal, Muh; Wulandari, Sri; Amiruddin; I Masita (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2026)
In the current digital era, the importance of effective archive management is increasingly evident for ensuring administrative efficiency, data security, and quality public services. This study aims to design a web-based archive information system for the Ta Village Office, Tanete Riattang District, Bone Regency. The Waterfall model was applied, covering needs analysis, system design, coding with PHP, HTML, CSS, JavaScript, and MySQL, as well as black-box testing. The system, involving the secretary and village head as users, successfully manages incoming and outgoing letters and certificates more quickly and accurately. Key features include digital archive management, quick search, activity history, and data export. Testing and user feedback confirmed that the system accelerates services, reduces the risk of data loss, and supports real-time access. Thus, the system offers an innovative solution to improve transparency, accountability, and service quality in village administration.